Quis custodiet ipsos custodes? – Who supervises the supervisors? - Kurt Bayer (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: The controversy still rages on whether the current crisis is the result of market failure or government failure. Paraphrasing former US-President Harry Truman's request for a one-armed economist, I would say both. On the one hand, the tenets of the mainstream efficient market hypothesis for explaining the functioning of financial markets, which formed the basis of their deregulation, have been glaringly shown to be wrong. On the other hand, it was the willing to-be-captured attitude of government actors, including regulators, which aided and abetted market failure. However, expectations about the imminent demise of neoliberal economics are premature, since to change the mainstream paradigm in economics will take a long time. This would require new curricula, new teachers, and a new generation of students, new textbooks, and new criteria for journal article acceptance. We also cannot just go back to Keynesian economics, since during the last decades many economic conditions – not least the new dominance of finance over the real economy – have changed, making some of Keynes's observations obsolete. Of course, many elements of a more realistic, less dogmatic economics exist already, viz. the essential writings of Hyman Minsky on the inherent instability of financial markets (see e.g. Minsky 1992), of behavioural economics, of institutional economics, but still unfettered belief in the invisible hand of the market persists to an astonishing degree.
Keywords: 330